Manajemen Pembelajaran Tauhid Pada Madrasah Aliyah Swasta Jabal Nur Dan Dayah Madinatuddiniyah Jabal Nur - Yuzi Arifin (DAYAH: Journal of Islamic Education, 2019)
This research is aimed to know: 1) planning of learning Akidah-Tauhid in MAS Jabal Nur and Dayah Madinatuddiniyah Jabal Nur, 2) the implementation of learning Akidah-Tauhid in MAS Jabal Nur and Dayah Madinatuddiniyah Jabal Nur, 3) the assesment of learning Akidah-Tauhid in MAS Jabal Nur and Dayah Madinatuddiniyah Jabal Nur. This research was conducted in MAS Jabal Nur and Dayah Madinatuddiniyah Jabal Nur to trial the instrument and conduct the research. Populations in this research are the students from grade X MAS Jabal Nur which consists of 4 classes, grade XI MAS Jabal Nur which consists of 4 classes, grade XII MAS Jabal Nur which consists of 3 classes, 2 teachers of subject Akidah-Tauhid in MAS Jabal Nur and 5 teungku of subject Akidah-Tauhid in Dayah Madinatuddiniyah Jabal Nur. The result of data analysis showed that the planning of Akidah-Tauhid in MAS Jabal Nur the teacher paid attention to some steps of planning. Otherwise, in Dayah Madinatuddiniyah Jabal Nur was applied curriculum of dayah salafi. In Dayah Madinatuddiniyah Jabal Nur is aided the method of reading classical book which distinguish between MAS and Dayah Madinatuddiniyah Jabal Nur. There is similarity of assesment of learning Akidah-Tauhid in conducting test/exam to know the development of student intellectual, the only differences is the form of questions between MAS and Dayah Madinatuddiniyah Jabal Nur.